Central kynurenine pathway shift with age in women. Issue 5 (20th January 2016) - de Bie, Josien; Guest, Jade; Guillemin, Gilles J.; Grant, Ross
Abstract: Age is considered a dominant risk factor in the development of most neurodegenerative disorders. The kynurenine pathway, a major metabolic pathway of tryptophan is altered in the majority of neurodegenerative disorders. In this study, we have analysed CSF samples from 49 healthy women across a wide age range (0–90) for kynurenine pathway metabolites and the inflammatory marker neopterin. Our results show central tryptophan metabolism is increased with age in women, with an apparent shift towards the neurotoxin quinolinic acid. We also observed an increase in central levels of the inflammatory marker neopterin with age and a positive correlation between neopterin and kynurenine pathway activation. We conclude that, the changes that occur in the kynurenine pathway as a result of normal ageing are mechanistically linked to increased inflammatory signalling and have some explanatory potential with regard to age‐associated degenerative diseases in the CNS. Management of health in ageing and (preventative) treatment would do well to look to the kynurenine pathway for potentially novel solutions. Both the inflammation marker neopterin and kynurenine pathway activity were increased with age in the CSF of female subjects. While levels of quinolinic acid (QUIN), picolinic acid (PIC), kynurenine and quinaldic acid (QA) were increased, 3‐hydroxykynurenine (3HK) was decreased and 3‐hydroxyanthranilic acid (3HAA) and kynurenic acid (KYNA) remained unchanged. Of particular interest is the increase in QUIN, a neuroexcitotoxin associated with neurodegeneration. Abstract : Both the inflammation marker neopterin and kynurenine pathway activity were increased with age in the CSF of female subjects. While levels of quinolinic acid (QUIN), picolinic acid (PIC), kynurenine and quinaldic acid (QA) were increased, 3‐hydroxykynurenine (3HK) was decreased and 3‐hydroxyanthranilic acid (3HAA) and kynurenic acid (KYNA) remained unchanged. Of particular interest is the increase in QUIN, a neuroexcitotoxin associated with neurodegeneration.